Osmanlı Devleti’nde Zorunlu Askerliğe Direniş: ‘Muînsiz’ Efrad Problemi - Rıza ÖZBÖLÜK (Gazi Akademik Bakış)
The conscription that was put into effect in 1846, in the Ottoman Empire, could not be implemented at the desired level due to conflicts between priorities of the state and socioeconomic realities of the society. Men who did not want to be included within the limits of this obligation actually tried to avoid military service by using the laws and regulations that determined the legal framework of conscription. In this context, unprecedented opportunities were created, especially in the exemption categories in the conscription laws. Those who did not want to do their military service or have any conflicts with the state made themselves suitable for the exemption categories by various methods. In this context, one of the most used methods by the individuals was to present themselves like a muînsiz [breadwinner] and provide exemption. Since this method was widely applied, the compulsory military system became inextricable and finally, the exemption categories were abolished just before the World War One.